Incidence, risk factors and clinical implications of postoperative urinary tract infection in geriatric hip fractures. Issue 6 (June 2022) - Saadat, Ghulam H; Alsoof, Daniel; Ahmad, Bilal; Butler, Bennet A; Messer, Thomas A; Bokhari, Faran
Highlights: There is limited evidence on risk factors and effects of postoperative UTI in the geriatric hip fracture patient population. Older age (≥85 years), patients with severe systematic diseases (ASA≥ 3), blood transfusion, and delay beyond 2 days to operate are associated with postoperative UTI. Postoperative UTI is associated with a significant increase in sepsis, postoperative length of stay, and readmission. Understanding the risk factors and clinical impact of postoperative UIT may help achieve better outcomes in geriatric patients with hip fractures. Abstract: Introduction: Postoperative urinary tract infection (UTI) is common in geriatric patients; however, little is known about the impact of UTI in orthopedic trauma. The present study was designed to determine the risk factors and clinical impact of postoperative urinary tract infection (UTI) in acute geriatric hip fractures. Patients and methods: Geriatric patients (≥65 years of age) undergoing hip fracture surgery were identified within the American College of Surgeons National Surgical Quality Improvement Program between 2016 and 2019. Patients presenting with UTI at the time of surgery were excluded. Baseline characteristics and outcomes were compared between patients with and without postoperative UTI. Multivariate logistic regression was performed, controlling for potential confounders. Results: A total of 46, 263 patients included in the study. Overall, 1, 397 (3.02%) patients had postoperative UTI. Patients who developed postoperative UTI had higher rates of pneumonia (6.44% vs. 3.76%, p < 0.001), DVT (2.22% vs. 1.04%, p < 0.001), sepsis (7.73% vs. 0.62%, p < 0.001), and more frequently experienced postoperative hospital lengths of stay exceeding 6 days (37.94% vs. 20.33%, p < 0.001). Hospital readmission occurred more frequently in patients with postoperative UTI (24.55% vs. 7.85%, p < 0.001), but surprisingly, these patients had a lower mortality rate (1.36% vs. 2.2%, p < 0.001). Adjusted analysis demonstrated the following variables associated with postoperative UTI: age ≥ 85 (OR = 1.37, 95%CI = 1.08 - 1.73), ASA class ≥ 3 (OR = 1.59, 95%CI = 1.21 – 2.08, ), chronic steroid use (OR = 1.451, 95%CI = 1.05 - 1.89), blood transfusion (OR = 1.24, 95%CI = 1.05 - 1.48), and >2 days delay from admission to operation (OR = 1.37, 95%CI = 1.05 - 1.79). Postoperative UTI was significantly associated with sepsis (OR = 7.65, 95%CI = 5.72 – 10.21), postoperative length of stay >2 days (OR = 1.83, 95%CI = 1.07 – 3.13), and readmission (OR = 3, 95%CI = 2.54 – 3.55). Conclusions: In our study, postoperative UTI was found in 3% of geriatric hip fracture patients. Predictors of postoperative UTI were age ≥ 85, ASA class ≥ 3, chronic steroid use, blood transfusion, and time to operation > 2 days from admission. Results showed that postoperative UTI is independently associated with sepsis, postoperative length of stay beyond 2 days, and hospital readmission. To diminish the risk of UTI and its consequences, we recommend operating geriatric hip fractures in 24–48 hours after admission.